Digital Communication Strategy to Increase Visibility of Women's MSMEs: A Case Study of Padang City - Annisa Weriframayeni; Sri Mona Octafia; Elsa Widia (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Women's participation in Indonesia's economy has long been a focus of attention. Notably, more than 60 percent of MSMEs (Micro, Small, and Medium Enterprises) in Indonesia are managed by women. While numerous studies have examined how digitalization impacts MSME performance in Padang City, there has been little to no specific research on effective communication strategies in the digital realm. Therefore, this study aims to provide comprehensive and relevant insights for developing effective digital communication strategies to enhance the marketing performance of women-owned MSMEs in Padang City. The study includes an in-depth analysis of the types of digital platforms used, the messages conveyed, and the ways interactions with customers are conducted through social media, websites, or e-commerce platforms. The research methodology involves the collection of primary data through in-depth interviews and surveys, as well as secondary data related to the profiles of women-owned MSMEs. The data analysis employs multivariate regression analysis to identify the influence of several independent variables on multiple dependent variables simultaneously.The results indicate that strategies involving the use of social media and online advertisements are highly effective in increasing the visibility of MSMEs on social media platforms. Meanwhile, using websites and online advertisements proves to be more effective in driving visitors to the MSME websites.